Cauda Equina Syndrome: Poor Recovery Prognosis Despite Early Treatment. Issue 2 (15th January 2022) - Planty-Bonjour, Alexia; Kerdiles, Gaelle; François, Patrick; Destrieux, Christophe; Velut, Stephane; Zemmoura, Ilyess; Cook, Ann-Rose; Terrier, Louis-Marie; Amelot, Aymeric
Abstract : Study Design: A prospective patient's database operated on a cauda equina syndrome (CES). Objective: The aim of our study was to identify prognosis factors for favorable functional recovery after CES. Summary of Background Data: CES is a neurologic impairment of variable symptoms associating urinary, bowel, and sexual dysfunctions with or without motor or sensitive deficits caused by nerve root compression of the cauda equina. The definition of CES remains debated, as well as the prognosis factors for favorable functional recovery and the benefit of early surgery. Methods: One hundred forty patients were included between January 2010 and 2019. Univariate and multivariate cox proportional hazard regression models were conducted. Results: The patients were young with a median age of 46.8 years (range 18–86 yrs). At presentation, 60% were affected by a motor deficit, 42.8% a sensitive deficit, 70% urinary dysfunctions, and 44% bowel dysfunctions. The mean follow-up was 15.5 months. Bilateral motor deficit ( P = 0.017) and an initial deficit severity of 0 to 2 ( P = 0.001) represented prognosis factors of poor motor recovery. Initial anal incontinence ( P = 0.007) was associated with poor bowel recovery. Only 32.8% of the patients went back to work. Initial motor deficit ( P = 0.015), motor sequelae ( P = 0.001), sphincter dysfunctions sequelae ( P = 0.02), and long LOS ( P = 0.02) were poor return-to-work prognosis factors. Time to surgery within an early timing < 24 or 48 hours or later did not represent a prognosis factor of recovery in CES. Incomplete versus complete CES did not show better recovery. Conclusion: CES remains a profound disabling syndrome with poor functional prognosis: in the long run, few patients go back to work. The main prognosis factors established in our series regarded the initial severity of deficits whether motor or sphincteral. Early or later surgical cauda equina decompression did not show to represent a prognosis factor for functional recovery. Level of Evidence: 4 Abstract : Cauda equina syndrome (CES) remains a profound disabling syndrome. The prognosis factors for favorable functional recovery and the impact of early surgery were fuzzy. We determined that the main prognosis regarded the initial severity of deficits whether motor or sphincteral. Early surgery did not show to represent a prognosis factor.